2012
DOI: 10.4236/as.2012.35080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different levels of humic acid and esterified glucomannan on growth performance and intestinal morphology of broiler chickens

Abstract: A study was under taken to investigate the effect of dietary supplementations of humic acid and esterified glucomannan) on broiler performance and the morphological measurements of small intestine. Two hundred and ten day old broiler chicks were weighed and randomly assigned to seven treatment groups in triplicate. The dietary treatments included T1) control (basal diet without any additives), T2) basal diets supplemented with 0.1% humic acid, T3) basal diets supplemented with 0.2% humic acid, T4) basal diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
34
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 18 publications
12
34
2
5
Order By: Relevance
“…The highest body weight on the 42. day of fattening was recorded in the first experimental group of chickens fed a diets containing only humic acids but the different treatments were not statistically significant. Our results are in agreement with Taklimi et al (2012) or Lala et al (2017) who likewise recorded significantly increased weight gain by adding of humic acid. Miloševic et al 2013reported that supplementation of 1.5% and 3.0% of garlic powder had significant positive effect of body mass (P <0.05).…”
Section: Resultssupporting
confidence: 93%
“…The highest body weight on the 42. day of fattening was recorded in the first experimental group of chickens fed a diets containing only humic acids but the different treatments were not statistically significant. Our results are in agreement with Taklimi et al (2012) or Lala et al (2017) who likewise recorded significantly increased weight gain by adding of humic acid. Miloševic et al 2013reported that supplementation of 1.5% and 3.0% of garlic powder had significant positive effect of body mass (P <0.05).…”
Section: Resultssupporting
confidence: 93%
“…In rats supplemented with HS, higher nitrogen retention has also been observed [39]. Recently, in FA-fed broilers [40] higher activities of the digestive enzymes amylase, lipase, and protease were reported, which agrees with the increased length of the mucosal villi of the jejunum and the increased gut length due to dietary inclusions of HS in broiler [12,41]. However, these findings do not agree with the lack of effects of EHS on nutrient use in our research.…”
Section: Effect Of Dietary Treatmentscontrasting
confidence: 52%
“…Similar results were reported by Hanafy and El-Sheikh (2008); Sahin et al (2011) and Taklimi et al (2012), who found that feed consumption was not affected significantly by humic acid supplementation.…”
Section: Live Body Weightsupporting
confidence: 90%
“…However, hens in all treatment groups were significantly (P<0.05) heavier than the controls, being the heaviest in T3 at 52 wk of age. These results are in agreement with those reported by Hanafy and El-Sheikh (2008), who indicated that live body weight was significantly (P≤0.05) increased by age of laying hens as affected by humic acid supplementation.In this respect, several authors indicated that humic acid had a positive effect on live body weight of laying hens (Shermer et al, 1998), broilers (Ozturk et al, 2012;Taklimi et al, 2012;Mirnawati and Marlida, 2013) and Japanese quail (Abdel-Mageed, 2012).…”
Section: Live Body Weightmentioning
confidence: 99%